2008
DOI: 10.1093/intimm/dxn060
|View full text |Cite
|
Sign up to set email alerts
|

IL-33 amplifies both Th1- and Th2-type responses through its activity on human basophils, allergen-reactive Th2 cells, iNKT and NK Cells

Abstract: IL-33 is an IL-1 family member recently identified as the ligand for T1/ST2 (ST2), a member of the IL-1 receptor family. ST2 is stably expressed on mast cells and T(h)2 effector T cells and its function has been studied in the context of T(h)2-associated inflammation. Indeed, IL-33 induces T(h)2 cytokines from mast cells and polarized mouse T cells and leads to pulmonary and mucosal T(h)2 inflammation when administered in vivo. To better understand how this pathway modulates inflammatory responses, we examined… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

39
541
4
11

Year Published

2009
2009
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 554 publications
(595 citation statements)
references
References 39 publications
39
541
4
11
Order By: Relevance
“…The cytokine expression pattern of T cells polarized by IL-33-activated DCs differs from classical Th2 cells by the absence of IL-4 production. An atypical Th2 subset upon IL-33 activation has been reported, which is independent of IL-4, GATA3 and TCR engagement [26,29].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The cytokine expression pattern of T cells polarized by IL-33-activated DCs differs from classical Th2 cells by the absence of IL-4 production. An atypical Th2 subset upon IL-33 activation has been reported, which is independent of IL-4, GATA3 and TCR engagement [26,29].…”
Section: Discussionmentioning
confidence: 99%
“…IL-33 signals through a heterodimeric membrane receptor composed of ST2 and the IL-1R1 accessory protein and activates basophils [20,21], mast cells [22,23], eosinophils [24,25], NK and NKT cells [26], Th2 lymphocytes [5,27] and macrophages [14]. In accordance with its Th2 functions, administration of IL-33 into naive mice induces severe inflammation in the lung and digestive tract with elevated levels of IL-4, IL-5 and IL-13, splenomegaly and increased serum Ig [10].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…IL-33 appears to be predominantly expressed in vivo in endothelial and epithelial cells [20,21], but IL-33 expression may be induced by inflammatory signals in other cell types [11,22]. Cell targets of IL-33 include polarized Th2 cells [11,23,24], mast cells [15,25], basophils [24,26], and dendritic cells [27,28]. Besides these ST2-receptor mediated effects, IL-33 is able to translocate into the nucleus, where it may display transcriptional functions.…”
Section: Introductionmentioning
confidence: 99%
“…8,9 As a nuclear factor, the intracellular functions of IL-33 remain to be further clarified, although overexpression studies suggested a role as a transcriptional repressor. 10 As an extracellular cytokine, binding of IL-33 to the ST2 receptor activates nuclear factor-kB and mitogen-activated protein kinases, [3][4][5]11 and is involved in the polarization of T cells towards the Th2 cell phenotype 2,6,7,[11][12][13][14] and in activation of mast cells, [15][16][17][18][19][20] bosophils, 14,[20][21][22][23][24] eosinophils, [24][25][26] and natural killer cells. 14,27 IL-33 must be present extracellularly in order to play the crucial role in inflammatory, infectious and autoimmune diseases including anaphylactic shock, asthma, rheumatoid arthritis, atherosclerosis, systemic sclerosis and cardiovascular diseases.…”
Section: Introductionmentioning
confidence: 99%